MAQĀṢID AZ-ZUWĀJ ASY-SYARʿIYYAH; DIRĀSATUN LI-AHAMM MAQĀṢID AZ-ZAWĀJ AL-AṢLIYYAH WA AT-TABAʿIYYAH - Firano, Ismail (Institut Agama Islam Negeri Bone, 2024)
The essence of Islamic law lies in promoting and fulfilling the well-being of people while preventing and minimizing harm in their religious and worldly affairs. Therefore, understanding the objectives of Sharia in the institution of the family is crucial and urgent, especially given the immense challenges faced by Muslim societies today. The primary path to family formation is marriage, which, according to the Quran, is not merely a means for preserving the human race but also a way to achieve psychological reassurance, inner peace, and emotional tranquility. Islam places great emphasis on the family, providing care and guidance, and outlining the paths that enable it to fulfill its roles in building a strong society characterized by righteousness, justice, love, compassion, harmony, and happiness. To delve deeper into this topic, this study employed a qualitative research methodology, relying on primary sources from the Quran and Sunnah, and secondary sources from books of Tafsir (Quranic exegesis), Fiqh (Islamic jurisprudence), and Usul al-Fiqh (principles of Islamic jurisprudence). When God Almighty connects marriage to the sexual instinct, it is not merely for the fulfillment of desire, but rather to achieve higher purposes, such as establishing the family as the foundation of society and raising children according to the wise principles of Sharia. Therefore, God has established pillars and conditions for marriage, along with objectives and goals. When these are observed, marriage fulfills its positive impacts on various aspects of society. However, neglecting these objectives disrupts the intended purpose of marriage, leading to dysfunction, marital and social problems, and a deviation from the purity, love, and serenity that are desired for life. These problems can only be addressed by preserving, caring for, and upholding the true objectives of marriage. إن الشريعة الإسلامية لها روح وهي جلب مصالح العباد وتكميلها، ودفع المفاسد عنهم وتقليلها في دينهم ودنياهم، ومن هنا فإن الكشف عن مقاصد الشريعة في مؤسسة الأسرة أمر ضروري وملح، تزداد الحاجة إليه في ظل التحديات الهائلة التي تعيشها المجتمعات المسلمة قاطبة. والسبيل الأول لتكوين الأسرة هو نظام الزواج الذي يعد في حكم القرآن ليس وسيلة لحفظ النوع الإنساني فقط، بل هو فوق ذلك وسيلة للاطمئنان النفسي والهدوء القلبي والسكن الوجداني، ولما كان الأمر كذلك اهتم الإسلام بالأسرة وأحاطها برعايته وعنايته، ورسم لها السبل التي تؤهلها للقيام بمهامها في بناء مجتمع قوي يسوده الصلاح والعدل، وتنتشر فيه روح المودة والمحبة والألفة، وترفرف عليه أعلام السعادة والهناء .وللتعمق في هذا الموضوع، اعتمدت هذه الدراسة على منهجية البحث المكتبي، بالاعتماد على مصادر أولية من القرآن الكريم والسنة النبوية، ومصادر ثانوية من كتب التفسير والفقه وأصول الفقه وحينما يربط الله تعالى الزواج بغريزة الجنس لم يكن ليقصد مجرد قضاء الشهوة، بل قصد أن يكون على النحو الذي يحقق تلك المقاصد العظيمة المتمثلة في تكوين الأسرة عمادِ المجتمع، وتربية الأبناء وفق قواعد الشرع الحكيم، فلذلك تجده سبحانه جعل للزواج أركانا وشروطا لا يتحقق بدونها، كما جعل له مقاصد وأهدافا وغايات إذا روعيت حقق آثاره في المجتمع في شتى مناحي الحياة، وإذا أهملت تلك المقاصد أو أخل بها لم يتحقق المعنى المقصود من الزواج، وتعطلت الحياة واضطربت، وظهرت المشكلات الزوجية والاجتماعية، وتزداد هذه المشكلات على حسب ما يهمل من تلك المقومات والمقاصد، ولا يمكن علاجها والعودة بالحياة إلى ما يرجى لها من طهر وود وصفاء، إلا بالحفاظ على تلك المقاصد والعناية بها ورعايتها حق رعايتها